Strategi Strategi Penggalangan Dana Pada Organisasi Kemanusiaan Berbasis Agama : Studi Deskriptif Penggalangan Dana Di Dompet Dhuafa - Fauzia, Herlin Rahma (Jurnal Ilmu Kesejahteraan Sosial, 2014)
This study discuses about strategies of fundraising conducted by Yayasan Dompet Dhuafa with the supports and obstacles. This study used qualitative method and descriptive approach. The result of study show that Dompet Dhuafa have some strategies of fundraising. First, retail fundraising includes counter, Gerakan Donasi, Jemput Zakat and direct mail. Second is partnership with companies, another institutions and public